Parâmetros Genéticos para a Produção de Leite, Gordura e Proteína em Bubalinos - Tonhati, H.; Munoz, MFC; de Oliveira, J. A.; Duarte, JMC; Furtado, T. P.; Tseimazides, S. P. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2000)
The objective of this study was to estimate the genetic parameters affecting milk production (MP), fat (%F) and protein (%P) contents of buffalo milk. Restricted Maximum Likelihood (REML) using MTDFREML program under animal model analyzed a total of 1744 lactations records from 1268 cows. The means were: MP = 1259.47 +/- 523.09 kg, %F = 6.87 +/- 0.88% and %P = 3.91 +/- 0.61%. The estimates of repeatability and heritability coefficients were: MP = 0.38 and 0.24, %F = 0.28 and 0.21 and %P = 0.30 and 0.26, respectively. The estimated genetic and phenotypic correlations were MP x %F = -0.18 and -0.62, MP x %P = -0.23 and -0.59 and %F x %P = 0.50 and 0.77, respectively. According to these results it is possible to conclude that selection is a proper way to increase milk yield, fat and protein percentage. Although negative low values of genetic correlations among traits, it should be take into account that simultaneous selection based on these traits could not be so efficient.
Genetic parameters of milk production, fat and protein contents in buffalo milk
Keywords: Búfalo; Genetic correlation; Heritability; repeatability